The Mindset of Kalmyks: origins and causes of alterations - Chetyrova, Lyubov B. (The New Research of Tuva, 2017)
The article examines the issue of origins and specific features of the mindset of Kalmyks. The categories of honor and dignity, very important for Kalmyks, are proved to be of military origin. The article traces how a change in Kalmyk practices led to corresponding alterations in menthal structures. Our analysis in the theoretical aspect is based on the theory of habitus developed by P. Bourdieu and phenomenology of the Other (Alien) as explicated by E. Husserl, E. Lévinas, B. Waldenfels and A. Schütz. The author highlights several key moments in the history of Kalmyks that helped shape and alter the mindset of Kalmyks, such as annexation to Russian Empire, the heyday of Kalmyk Khanate, the relocation of the majority of Kalmyks to Dzungaria, the rise of administrative and economic structures in post-khanate period, large-scale departure for seasonal works in mid-19th century, two revolutions, the Soviet modernization project, WWII and the deportation to Siberia, the subsequent restoration of autonomy, and finally, the post-Soviet period. The article analyzes the mindset of Kalmyks is analyzed within the framework of Empire studies, which allows to focus on the evolution and alterations in mindset of Kalmyks as an imperial ethnos. Ethnogenesis of Oyrats occurred within the military and political domain of Mongol Empire, Kalmyks as ethnos arose in the ethnopolitical landscape of Russian Empire, and Kalmyks as nation appeared within the “empire of nations” – USSR. The author shows that the construction of a new nation and identity of Kalmyks in the post-Soviet period also affected their mindset. The article is based on the studies of the documents preserved at the National Archive of the Republic of Kalmykia, pre-revolutionary literature and periodicals of the early Soviet period.